2012
DOI: 10.1002/hbm.22135
|View full text |Cite
|
Sign up to set email alerts
|

Neural adaptation to thin and fat bodies in the fusiform body area and middle occipital gyrus: An fMRI adaptation study

Abstract: Visual perception can be strongly biased due to exposure to specific stimuli in the environment, often causing neural adaptation and visual aftereffects. In this study, we investigated whether adaptation to certain body shapes biases the perception of the own body shape. Furthermore, we aimed to evoke neural adaptation to certain body shapes. Participants completed a behavioral experiment (n = 14) to rate manipulated pictures of their own bodies after adaptation to demonstratively thin or fat pictures of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 61 publications
(111 reference statements)
6
37
2
Order By: Relevance
“…In line with our predictions, observers showed aftereffects of body size after prolonged viewing of large and small bodies (main effects of adaptation direction). These results are consistent with past research regarding body size adaptation, which found that size aftereffects occur such that the point of perceived normality shifts in the direction of the adapting bodies171820213637.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our predictions, observers showed aftereffects of body size after prolonged viewing of large and small bodies (main effects of adaptation direction). These results are consistent with past research regarding body size adaptation, which found that size aftereffects occur such that the point of perceived normality shifts in the direction of the adapting bodies171820213637.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies manipulated images by stretching the entire image horizontally21, by expanding the image principally around the waist-hip region17, through the distortion of different body “zones”36, or by manipulating computer generated bodies18. Instead, we used advanced image morphing techniques to create more realistic manipulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fusiform gyrus is an important structure in external body recognition 51 and body size perception. 52 Importantly, previous research found GM and WM in this area related to body weight changes, 53 and this region is consistently activated when viewing food images. 54 Furthermore, hippocampus and parahippocampus show decreased activation during satiety states.…”
Section: Discussionmentioning
confidence: 90%